They Will Do Anything to Make You React: Deplatforming Racists from the Brazilian Gaming Community - Araujo Caetano, Mayara (Gamevironments, 2022)
This article discusses the deplatforming of a racist content creator and streamer from the Brazilian gaming community. It raises questions about the extent of success of deplatforming when platforms are also structurally oppressive. The case being discussed started after racist harassment during #BlackLivesMatter mobilisation after Floyd; and was led by players, creators, and allies aiming for an anti-racist gaming environment in Brazil. Narrative interviews (Rosenthal 2018) were conducted with the victims and articulators to understand the construction of this coalition. Their testimonies, combined with social media materials collected during and after the event, were analysed using the intersectional roulette (Carrera 2021) and show how platform structures, companies, and Institutions present significant obstacles in enforcing their Community Guidelines, Terms of Use, reporting system, and compliance with the Law. Nevertheless, it is still a noteworthy case of social justice, representing how the strategic use of technologies can benefit collective engagement.